The Problem of Property in the Austrian School of Economics - Kargol-Wasiluk, Aneta; Zalesko, Marian; Pietrzak, Małgorzata (Studia Historiae Oeconomicae, 2011)
The issue of property and ownership has been discussed in many economic doctrines. The authors' intention is to examine property in terms of the Austrian School of Economics. Ownership is here regarded as an integral part of freedom, whereby the owner of a particular good has an unrestricted right to use it. In the economy of most importance is private property which is unhampered by any restrictions. It is just on its foundations that any economic system should be based. The authors of this study attempt to verify a hypothesis that any restrictions on private property contribute to a reduction in economic efficiency. Analysis of the problem is carried out based on the views of eminent representatives of the School. Most of the attention will be devoted to the thought of F. von Hayek and L. von Mises.